Epratuzumab modulates B‐cell signaling without affecting B‐cell numbers or B‐cell functions in a mouse model with humanized CD22. Issue 9 (25th July 2016) - Özgör, Lamia; Brandl, Carolin; Shock, Anthony; Nitschke, Lars
Abstract : In this study, we aimed to understand the function of the clinical anti‐CD22 antibody epratuzumab using a knockin mouse model, which expresses human CD22 instead of murine CD22 on B‐cell surface. We found that epratuzumab neither influences B‐cell numbers nor B‐cell functions, but decreases B‐cell signaling . Abstract : Treatment of systemic lupus erythematosus patients with epratuzumab (Emab), a humanized monoclonal antibody targeting CD22, leads to moderately reduced B‐cell numbers but does not completely deplete B cells. Emab appears to induce immunomodulation of B cells, but the exact mode of action has not been defined. In the present study, we aimed to understand the effects of Emab on B cells using a humanized mouse model (Huki CD22), in which the B cells express human instead of murine CD22. Emab administration to Huki CD22 mice results in rapid and long‐lasting CD22 internalization. There was no influence on B‐cell turnover, but B‐cell apoptosis ex vivo was increased. Emab administration to Huki CD22 mice had no effect on B‐cell numbers in several lymphatic organs, nor in blood. In vitro exposure of B cells from Huki CD22 mice to Emab resulted in decreased B‐cell receptor (BCR) induced Ca 2+ mobilization, whereas B‐cell proliferation after Toll‐like receptor (TLR) stimulation was not affected. In addition, IL‐10 production was slightly increased after TLR and anti‐CD40 stimulation, whereas IL‐6 production was unchanged. In conclusion, Emab appears to inhibit BCR signaling in a CD22‐dependent fashion without strong influence on B‐cell development and B‐cell populations.